Combination of Diamond Painting Play Therapy and Music Therapy on Fine Motor Development in Preschool Children - Lensiana Novi; Eni Susanti Laia; Nurmawati S. Lataima; Shinta Wurdiana R; Hendro Djoko Tjahjono (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: One of the factors that influences fine motor development is stimulation. Children who receive more stimulation will develop faster than those who rarely do (4). Some activities that can develop fine motor skills include puzzle games. One type of puzzle that is currently popular in children's environments because it is interesting and easy to get is diamond painting. Diamond painting is a drawing game on a canvas by attaching diamond-shaped beads to a pattern that is already available. This game can train children's fine motor skills because the child's fingers will move to attach the beads to the painting media, in addition it can improve eye, hand coordination, concentration, and increase imagination and creativity. Not only play therapy or the use of other learning media, it turns out that music therapy can also improve children's motor development. Innovation and modification of play therapy need to be done in developing learning media so that they can help stimulate the growth and development of preschool children. objective: to analyze the effect of a combination of diamond painting play therapy and music therapy on fine motor development in preschool children. Method: This study uses a mixed method design, namely combining quantitative and qualitative methods in a study with an Explanatory Design approach. Result: fine motor skills of children in the intervention group with a p value of 0.000 or <0.05, meaning that there is an effect after being given a combination of diamond painting play therapy and music therapy.